Medieval Women: Voices and Visions, British Library exhibition review - Kierri Price (Science Museum Group Journal)
Dr Kierri Price reviews the Medieval Women: In Their Own Words exhibition at the British Library, with interjections from four fellow medievalists to reflect the excitement of the exhibition. Dr Price’s interlocutors include Dr Diane Heath (medievalist and a guest editor of this issue of the journal), Professor Louise Wilkinson from the University of Lincoln (who was on the advisory panel for the exhibition), Dr Harriet Kersey (expert in noblewomen of the thirteenth century), and Dr Sheila Sweetinburgh (Principal Research Fellow and Co-Director of the Centre for Kent History and Heritage at Canterbury Christ Church University).